Interaction of Mechanical Heterogeneity and Residual Stress on Mechanical Field at Crack Tips in DMWJs - Yubiao Zhang; He Xue; Shun Zhang; Shuai Wang; Yuman Sun; Yonggang Zhang; Yongjie Yang (Science and Technology of Nuclear Installations)
The interaction between the mechanical heterogeneity and the residual stress in dissimilar metal welded joints (DMWJs) leads to a complex mechanical field of crack tips, which strongly affects stress corrosion cracking (SCC) behaviors. A dual-field coupling model was established by using the user-defined field (USDFLD) and the predefined stress field method based on the elastoplastic finite element method in this study. Thus, the mechanical heterogeneity and the residual stress of the DMWJ are realized. The influence of the interaction between the mechanical heterogeneity and the residual stress on the mechanical field of crack tips at different locations was investigated. The results show that the mechanical heterogeneity causes the stress and strain distribution on both sides of the crack tip asymmetry. And the residual stress affects the magnitude of the stress and strain around the crack tip. The variation trend of the stress and strain along the crack propagation with crack length is basically the same as that of the residual stress. However, the stress and strain distributions are slightly lagging behind the residual stress distribution due to the redistribution of the residual stress caused by the crack propagation. In addition, the stress and strain range of cracks at different positions with crack length are also different.